Tensile and thermal properties of tapioca starch/ sugarcane bagasse cellulose biocomposite films - Wart a/p ehing (School of Material Engineering, University Malaysia Perlis, 2016)
Cellulose was extracted from raw sugarcane bagasse (SCB) through chemical route such as alkaline treatment and bleaching process. Cellulose obtained was characterized and compared by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). FTIR results show the reducing peak that related to non-cellulosic components after chemical treatment. XRD analysis showed that cellulose has higher crystallinity compared to raw SCB. SEM images illustrated the reducing in diameter of fibre and increasing of roughness after undergoing chemical treatment. TGA analysis revealed that cellulose has better thermal stability than raw SCB. The composite film of tapioca starch and cellulose had been characterized and tested by XRD, SEM, TGA, and tensile testing. XRD results show that composite with 5 phr cellulose has highest intensity and crystallinity. SEM images of tensile surface fracture proved the good interaction between filler and matrix for 5 phr cellulose content composite. TGA results show neat starch film has highest thermal stability while tensile testing revealed composite with 5 phr cellulose have the highest tensile strength and modulus of elasticity.